Effect of meloxicam on the number and weight of weaned piglets in primiparous sows - Ek-Mex, Jesús Enrique (2020)
The aim of this study was to evaluate the effect of the application of meloxicam in first-parity sows on the number of piglets born alive, and the number and weight of piglets at weaning in a commercial farm in the sub-humid tropics of Mexico. For this, 540 sows (270 sows per treatment) were used. The treated group received meloxicam (Metacam® 20 mg/ml, 0.4 mg/kg of body weight. IM) during farrowing and the control group was not treated. There were no significant differences for the variables under study between the two experimental groups.